2013
DOI: 10.1103/physrevlett.111.015003
|View full text |Cite
|
Sign up to set email alerts
|

Generating High-Brightness Electron Beams via Ionization Injection by Transverse Colliding Lasers in a Plasma-Wakefield Accelerator

Abstract: The production of ultra-bright electron bunches using ionization injection triggered by two transversely colliding laser pulses inside a beam-driven plasma wake is examined via three-dimensional (3D) particle-in-cell (PIC) simulations. The relatively low intensity lasers are polarized along the wake axis and overlap with the wake for a very short time. The result is that the residual momentum of the ionized electrons in the transverse plane of the wake is much reduced and the injection is localized along the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 27 publications
1
69
0
Order By: Relevance
“…This strategy has been demonstrated recently in two schemes utilizing an electron beam driver to excite the wake [16,17]. Due to the much lower electric field of the electron beam driver, ionization of low IP atoms (e.g., H or Li) are used to excite the wake while the modest IP helium atoms can be used to provide the injected electrons, which requires a much lower laser intensity.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has been demonstrated recently in two schemes utilizing an electron beam driver to excite the wake [16,17]. Due to the much lower electric field of the electron beam driver, ionization of low IP atoms (e.g., H or Li) are used to excite the wake while the modest IP helium atoms can be used to provide the injected electrons, which requires a much lower laser intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the demands for high beam energies, these applications entail stringent requirements with regard to the beam quality. While a number of numerical studies [6][7][8][9][10][11] indicated the potential of PWFAs to generate high quality beams, one of the major challenges constitutes the preservation of these qualities during the witness beam extraction and transport to the interaction region. In addition, the beams may have to be transported in between successive plasma sections and re-injected without significant quality deterioration in staged acceleration concepts, such as proposed e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In one, electrons are born inside the wake through field ionization where the wake potential is near a maximum which eases the trapping threshold [12][13][14]. There are now numerous variations of this idea in which the injection and wake excitation are separated [15][16][17]. In the second, one or more laser pulses are used to trigger injection inside one plasma wake bucket [18][19][20][21].…”
mentioning
confidence: 99%